A Physiological Controller for Turbodynamic Ventricular Assist Devices Based on a Measurement of the Left Ventricular Volume. Issue 7 (21st November 2013) - Ochsner, Gregor; Amacher, Raffael; Wilhelm, Markus J.; Vandenberghe, Stijn; Tevaearai, Hendrik; Plass, André; Amstutz, Alois; Falk, Volkmar; Schmid Daners, Marianne
Abstract The current article presents a novel physiological control algorithm for ventricular assist devices (VADs), which is inspired by the preload recruitable stroke work. This controller adapts the hydraulic power output of the VAD to the end‐diastolic volume of the left ventricle. We tested this controller on a hybrid mock circulation where the left ventricular volume (LVV) is known, i.e., the problem of measuring the LVV is not addressed in the current article. Experiments were conducted to compare the response of the controller with the physiological and with the pathological circulation, with and without VAD support. A sensitivity analysis was performed to analyze the influence of the controller parameters and the influence of the quality of the LVV signal on the performance of the control algorithm. The results show that the controller induces a response similar to the physiological circulation and effectively prevents over‐ and underpumping, i.e., ventricular suction and backflow from the aorta to the left ventricle, respectively. The same results are obtained in the case of a disturbed LVV signal. The results presented in the current article motivate the development of a robust, long‐term stable sensor to measure the LVV.